2019
DOI: 10.1016/j.ejmech.2019.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Multi-target design strategies for the improved treatment of Alzheimer's disease

Abstract: Alzheimer's disease (AD) is a multifactorial syndrome resulting in profound misery and poses a substantial burden on human health, economy, and society throughout the world. Based on the numerous AD-related targets in the disease network, multi-target design strategy is a crucial direction to seek for enhanced therapy, and multi-target drugs have the ability to regulate more targets than single-target drugs, affecting the disease network with more potency. Herein, we highlight nine major targets associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(104 citation statements)
references
References 124 publications
0
104
0
Order By: Relevance
“…Thus, therapeutic strategies against free radical damage, protein oxidation, calcium and free radicals, tau and Aβ deposits, and phosphorylation may aid in the prevention of stroke-induced acceleration of dementia [175,176].…”
Section: Other Mechanismsmentioning
confidence: 99%
“…Thus, therapeutic strategies against free radical damage, protein oxidation, calcium and free radicals, tau and Aβ deposits, and phosphorylation may aid in the prevention of stroke-induced acceleration of dementia [175,176].…”
Section: Other Mechanismsmentioning
confidence: 99%
“…AD is a central nervous system degenerative disease that seriously threatens the health of the elderly. Modern pharmacological studies have shown that common pathological features of AD include β-amyloid (Aβ) plaques, excessive phosphorylation of Tau protein to form neurofibrillary tangles, reduction of acetylcholine transmitters and inflammatory responses, and neuronal loss [34,35].…”
Section: Pharmacological Effects Of Pinocembrinmentioning
confidence: 99%
“…Other combinations were found to be effective in metal chelating activity and antioxidant properties with less toxicity [237,239]. Similarly, combinations of AChE with GSK3β inhibitors, MAO inhibitors, metal chelators, NMDAR inhibitors, 5-HT receptor inhibitors, histaminic receptors inhibitors and phosphodiesterase inhibitors have been studied [240]. Some drugs designed in this way have been reported to alleviate AD.…”
Section: Drug Combinations As a Strategy For Ad Therapymentioning
confidence: 99%